Impressionable or immune? Examining the influence of marquee sellers in B2B secondary market platforms for IT products - Alhauli, Abdullah (2023)
Although digital platforms have become mainstream, there still remain some unanswered questions pertaining to managing platform ecosystems. One such unexplored question pertains to the effect of marquee sellers on the platform—marquee sellers arguably attract other sellers and buyers to the platform, thereby enhancing the platform’s value. In this paper, we study how adding a marquee seller to a business-to-business (B2B) secondary-market platform for IT products affects other sellers, in terms of the prices they obtain for comparable products. Using proprietary data on B2B secondary-market auctions obtained from a platform provider, we show that the entry of a marquee seller has a positive effect on the prices obtained by other sellers on the platform, reflecting a reference-price effect. We further show that this positive effect on final prices is moderated by the extent to which bidders are active on multiple seller sites on the same platform and the extent to which bidders participate in the marquee seller site. We explain these effects using theory in multihoming and involvement, in terms of how reference prices are set. Our work extends the platforms literature by considering the specific influence of a marquee seller on other sellers, thereby informing platform owners on the implications of the advice to add more marquee sellers to platforms. We also contribute to the literature on secondary markets for durable, used IT products, which are instrumental in reducing electronic waste and mitigating the environmental damage done by electronic products in landfills.